Micro-credentials for information literacy skills education development in academic libraries - Durodolu, Oluwole O.; Aitokhuehi, Oyeyemi Ololade; Akintolu, Morakinyo (Berkala Ilmu Perpustakaan dan Informasi, 2026)
Introduction. This paper investigates the role of micro-credentials and digital badges in reinforcing information literacy and professional development within academic libraries. It assesses the benefits and challenges of these tools in continuous education at the University of Lagos, Nigeria. Research Methods. Using a descriptive survey design, the study involved 406 undergraduate and postgraduate students selected via stratified random sampling from the Faculty of Education. Data Analysis. Data were collected using a validated questionnaire and analysed using descriptive statistics (frequency, percentage and mean). Hypotheses were tested using T-test and ANOVA at a 0.05 significance level. Results. The results show that overall participation was fairly low, even though respondents generally believed the programme was beneficial for improving employability and supporting lifelong learning. The analysis also found clear differences across age groups: older professionals were more actively involved than younger ones. Perceptions of benefit differed by level of education as well: participants with associate degrees rated the programme as most valuable, while those with doctoral degrees perceived the least benefit. Conclusion. Micro-credentials serve as vital tools for verifiable skill acquisition. However, tailored strategies are necessary to address demographic variations and increase adoption rates for effective professional development.